PENGEMBANGAN SUMBERDAYA MANUSIA MELALUI TRAINING NEEDS ASSESSMENT PADA KANTOR KEMENTERIAN AGAMA KOTA MAKASSAR - Usman, Usman; Jusriadi, Edi; Maklassa, Dg. (COMPETITIVENESS, 2020)
Makassar City Ministry of Religious Affairs is one of the government agencies that has a vision as a pioneer of national ethics, inspiration, and motivator for the creation of tolerance among religious people. Based on the observations, researchers found that most ASNs are less active in carrying out their work due to lack of motivation and adequate intellectual capital ability, causing obstacles, especially jobs that use technology media such as computers. This study aims to analyze the system of training needs assessment in the development of ASN human resources at the Office of the Ministry of Religious Affairs of Makassar City. This type of research is descriptive qualitative research. The data collection process is done by observation method, interview, documentation study, and website access. The research informant is the Head of the Ministry of Religious Affairs of Makassar City, Kasubag Staffing, and ASN who have attended training. The results of the study can be concluded that: 1) From the aspect of asn quality in the Office of the Ministry of Religious Affairs of Makassar City with indicators of education jejang shows that the quality of ASN is still low, as well as from the non-formal education aspect. This means that the level of ASN participation in following training is still low, 2) From the institutional aspects in the Office of the Ministry of Religious Affairs of Makassar City internally or independently there is no ASN human resources development program in the form of training that has been designed in the Strategic Plan and work program, and 3) The system of information networking training needs assessment (training needs assessment) in the development of ASN human resources at the Office of the Ministry of Religious Affairs of Makassar City has not been effective and efficient in supporting asn performance.Keywords: Training Needs Assessment, Human Capital Development. Intellectual Capital